2017
DOI: 10.1007/s10545-017-0115-6
|View full text |Cite
|
Sign up to set email alerts
|

AMP‐activated protein kinase activation in mediating phenylalanine‐induced neurotoxicity in experimental models of phenylketonuria

Abstract: Phenylketonuria (PKU), one of the most prevalent autosomal recessive disorders of amino acid metabolism, is characterized by abnormal accumulation of phenylalanine, which can lead to intellectual disability. The main pathologic changes in the central nervous system of untreated phenylketonuric patients are reductions in the number of axons, dendrites, and synapses in the brain. Such alterations are thought to be mainly associated with the toxic effects caused by phenylalanine. However, the underlying molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…It has also been suggested that phenylalanine in SBH may have a memory-enhancing effect, as it can act directly on BDNF to enhance brain and physiological signals [ 21 , 55 ]. Phenylalanine is an amino acid derived from the daily diet that is converted to tyrosine in the body, which is needed in the brain because it is a major constituent of the tyrosine kinase B receptor (TrkB) that acts as a BDNF receptor [ 56 ]. BDNF is a metabolic modulator in humans through dietary regulation, increased physical activity, and glucose metabolism [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that phenylalanine in SBH may have a memory-enhancing effect, as it can act directly on BDNF to enhance brain and physiological signals [ 21 , 55 ]. Phenylalanine is an amino acid derived from the daily diet that is converted to tyrosine in the body, which is needed in the brain because it is a major constituent of the tyrosine kinase B receptor (TrkB) that acts as a BDNF receptor [ 56 ]. BDNF is a metabolic modulator in humans through dietary regulation, increased physical activity, and glucose metabolism [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Observations from a previous study also highlighted the consistency of the phenylalanine in local stingless bee honey [33]. Phenylalanine is a dietary amino acid that is converted to tyrosine which occurs concurrently with the conversion of tetrahydrobiopterin to 4a-hydroxytetrahydrobiopterin and is catalysed by phenylalanine hydroxylase [43]. Tyrosine is needed in the brain as it is the main constituent of tyrosine receptor kinase B (TrkB) which plays a role as BDNF receptor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have found that UiPSCs preferentially differentiate into neurons and that even epithelial-like cells from human urine can directly differentiate into neural progenitor cells (20,21). Although studies have suggested that irreversible nerve damage due to a high concentration of phenylalanine in the blood may be related to brain-derived neurotrophic factor (22,23), no studies have thoroughly examined the mechanism whereby hyperphenylalaninemia results in mental retardation. PKU-UiPSCs provide a useful approach with which to understand the neurological effects of PKU since UiPSCs differentiate into neurons and the ability to create key cell types not directly available from patients with PKU.…”
Section: Discussionmentioning
confidence: 99%